2019
DOI: 10.3390/microorganisms8010059
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sequence Feature of SecA Translocase Protein Unique to the Thermophilic Bacteria: Bioinformatics Analyses to Investigate Their Potential Roles

Abstract: SecA is an evolutionarily conserved protein that plays an indispensable role in the secretion of proteins across the bacterial cell membrane. Comparative analyses of SecA homologs have identified two large conserved signature inserts (CSIs) that are unique characteristics of thermophilic bacteria. A 50 aa conserved insert in SecA is exclusively present in the SecA homologs from the orders Thermotogales and Aquificales, while a 76 aa insert in SecA is specific for the order Thermales and Hydrogenibacillus schle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 108 publications
(176 reference statements)
0
5
0
Order By: Relevance
“…It should be noted that while the SARS- and SARS-like viruses contain both CSIs ⑦and ❽, the RShSTT cluster of CoVs contains only the CSI ❽. Thus, it is likely that the CSI ⑦was introduced in the common ancestor of SARS-CoV-2r clade by either a secondary recombination event involving a SARS-related virus or independently by means of convergent evolution due to its selective advantage ( Gupta, 2018 ; Khadka, Persaud & Gupta, 2019 ). Based upon available information, we are unable to distinguish between these two possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that while the SARS- and SARS-like viruses contain both CSIs ⑦and ❽, the RShSTT cluster of CoVs contains only the CSI ❽. Thus, it is likely that the CSI ⑦was introduced in the common ancestor of SARS-CoV-2r clade by either a secondary recombination event involving a SARS-related virus or independently by means of convergent evolution due to its selective advantage ( Gupta, 2018 ; Khadka, Persaud & Gupta, 2019 ). Based upon available information, we are unable to distinguish between these two possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…The CSIs specific for different taxa also provide useful means for the development of sensitive and specific diagnostic tests using in silico and experimental methods (Ahmod et al, 2011;Wong et al, 2014). Lastly, the earlier work on CSIs show that these molecular characteristics are functionally important for the group of organisms for which they are specific (Singh and Gupta, 2009;Khadka et al, 2020). Hence, genetic, and biochemical studies on the identified CSIs could lead to the discovery of novel biochemical and/or other characteristics of different groups of organisms.…”
Section: Discussionmentioning
confidence: 98%
“…Lastly, the CSIs which are exclusively shared by a given group of organisms are the results of highly specific genetic/molecular changes (synapomorphies) [22,49,61]. Earlier work on these molecular markers show that the genetic changes represented by the CSIs are functionally important to the group of organisms, which contain them [62][63][64]. Hence, genetic and biochemical studies directed towards understanding the functional significance of these CSIs could provide information regarding novel biochemical and/or other characteristics of the specific groups of micro-organisms.…”
Section: Discussionmentioning
confidence: 99%